Family Christmas Dinner in Jerseyside (Charlie Walsh, Vince Walsh, Shirley Walsh, Monica Walsh, Des Walsh, Don Walsh) (1950)
Christmas at the house in Jerseyside, Placentia. Individuals photographed, if any, have been identified within the title from left to right.